The gender of the bear - Trott, Christopher (Études/Inuit/Studies, 2006)
AbstractThis article argues that there is an homological relationship between the symbolism surrounding the polar bear and the categorisation of gender among Inuit. In the first part of the paper, the broad implications of the significance of the bear are explored. The extensive debates around how to conceptualise Inuit gender categories are then summarised, focusing especially on the construction of a "third gender." These two apparently disparate fields of social thought are then brought together to propose a model that allows scholars to understand both the symbolic significance of bears and gender in a new way. Although the concept of a "third gender" has proved to be theoretically very powerful, it is inadequate to the data from Inuit who continue to hold two distinctive categories of gender. But unlike most other models, it allows for a passage connecting the two genres through which people can pass.